Analysis of changes in paper cutting forces during the cutting cycle in single-knife guillotine - Rusin, Agnieszka; Petriaszwili, Georgij (Univerzita Pardubice, 2013)
Paper presents the results of changes in the three components of cutting forces of paper stacks cutting during the cutting cycle in single-knife guillotine. The changes of the three components of cutting force at different stages of cutting cycle were analyzed.
Keywords: paper stack; cutting force; three components measuring; cutting cycle